Transformasi Struktur dan Konstruksi Masyarakat Wilayah Kukusan, Depok (1995-2010) - Ibrar, Muhammad Fasya (Socio Historica: Journal of Islamic Social History, 2023)
Research themes about microhistory and rural history are not commonly discussed and discovered, with the commonly researched history studies only covering the topic of macrohistory and urban history is easy to find, rather than microhistory and rural history. Kukusan area was a village founded before Depok City establish and has a long history as part of Particuliere Landerijen (Private Land) Land Pondok Tjina. Make Kukusan have historical imagination and memory collective in society. As traces part of Particuliere Landerijen (Private Land) in the past Kukusan had grown during that time to be perceived by residents in Kukusan on sectors social, economy, culture, education, and religious at many other revealed in other studies never be explained. These Studies use historical methods as a foundation with oral history forms from Kukusan community elders as actors from history and literature studies use document archives from individuals, organizations, and government. In other studies, the main topic of Kukusan Village focuses on the impact of Kukusan residents from movement the University of Indonesia to Depok only in sectors economic and social, never explaining the history of Kukusan. In this case, many people outside Kukusan never know the history of Kukusan. How Kukusan in the past can be grown and developed in many sectors social assimilation with urbanization, the economy from producing agriculture to service, culture with established identity Betawi Ora, and religiously with Muhammadiyah growth and massive widespread in Depok. The transformation had happened in Kukusan did not lose effect from factors internals and externals from the area surrounding it.                  Abstrak :Penelitian sejarah skala mikro dan sejarah desa atau kampung masih banyak belum dibahas pada saat ini, kecendrungan pembahasan penelitian tema sejarah skala makro dan sejarah kota lebih banyak ditemui dibandingkan dengan desa atau kampung. Wilayah Kukusan merupakan sebuah kampung yang ada sebelum kota Depok muncul, memiliki nilai sejarah yang Panjang sebagai wilayah kampung bekas dari bagian tanah partikelir Pondok Tjina. Membuat Kukusan memiliki gambaran historis dan memori kolektif yang membekas dalam masyarakatnya. Sebagai wilayah bekas tanah partikelir Kukusan dalam kurun waktu berlalu mengalami perkembangan yang dirasakan oleh masyarakat dari bidang sosial, ekonomi, budaya, pendidikan, dan keagamaan hal tersebut masih belum banyak dibahas dalam beberapa penelitian yang ada. Penelitian ini mengunakan metode sejarah dengan menggunakan metode sejarah lisan dari para tokoh masyarakat sebagai pelaku peristiwa sejarah dan metode studi pustaka dengan penggunaan dokumen arsip dari individu, organisasi, maupun pemerintah. Pada penelitian tentang Kukusan yang sudah ada lebih membahas pada pengaruh dari pindahnya Kampus UI terhadap masyarkat Kukusan hanya dari segi ekonomi dan sosial masyarakat yang pada dasarnya sejarah di masa lampau belum pernah dibahas. Dalam hal ini sejarah kampung Kukusan masih belum diketahui bagi beberapa masayarakat di luar Kukusan. Bagaimana Kampung Kukusan pada masa lalu sejarahnya bisa berkembang sampai saat ini dari sisi sosial dengan asimilasi dari datangnya kaum urban, sisi ekonomi yang berubah dari produsen agraris ke jasa, sisi budaya dengan munculnya sebutan Betawi Ora, dan sisi keagamaan dengan lahirnya Muhammadiyah di Kukusan dan berkembang di Kota Depok. Transfromasi yang terjadi di Kukusan tidak lepas dari faktor internal maupun eksternal dari lingkup wilayah yang ada di sekitarnya.